'Flat-out' formalism: Strong Island as trans-of-color critique. Issue 2 (3rd April 2021) - Jeffay, Tory
ABSTRACT: This article considers Strong Island, the Oscar-nominated documentary by Black, trans filmmaker Yance Ford about the murder of his brother, as a case study that allows us to think through questions of Blackness, transness, and visibility within the realm of documentary. The film refuses the forensic model of the juridical documentary, which seeks to uncover hidden truths and remedy particular miscarriages of justice. Instead, through an aesthetic emphasis on flatness that denies the viewer entry into the diegetic world, it forces us to confront more directly, for longer, and through specific eyes, the network of causes and consequences of the crime that were never hidden. Analyzing Strong Island 's formal strategies, I argue that the film reshapes the conventions of documentary – interview, b-roll, archival material – into a new visual grammar that highlights the limitations of visual evidence and mitigates the risks of visibility for Black and trans subjects. Ford rejects the standards of evidence inherent to both the legal system and the documentary film, instead fabulating, reaggregating, and producing counter-forensic evidence so that landscape, family snapshot, and his own body become implicated in his brother's murder.